Modulating urban dynamics from a climate perspective – In-between spaces and climate neutrality - Fabrizio Tucci; Paola Altamura; Maria Michaela Pani (Agathón)
This contribution presents the results of a study that interprets in-between spaces as a modular system which structures space, relationships, and urban dynamics from a climate perspective. The aim is to demonstrate the positive contribution that technological-environmental design can offer in the context of redevelopment and new construction of the urban fabric, concerning the ecological performance of the entire urban system, particularly from the perspective of decarbonisation and climate mitigation. Within this research, a methodology for classifying and analysing in-between spaces was developed, as well as a method for evaluating the reduction of climate-altering emissions. The paper compares six case studies that represent the three identified categories of in-between spaces, evaluating them through the criteria of Naturalness, Proximity and Circularity and in relation to the six strategic axes of Green Cities.